The fiscal and distributional impact of possible tax reforms in the Netherlands - Klaas de Vos (University of Essex, Institute for Social and Economic Research (ISER), 2012)
This paper uses the tax-benefit microsimulation model EUROMOD to assess how three types of tax reform would affect the state budget and the income distribution in the Netherlands. After briefly introducing the Dutch tax system and the case for and against these reforms, we investigate the effects of (1) introducing a flat income tax rate, (2) reducing the mortgage interest deduction and (3) shifting the state pension contribution to income tax, and of combining these reforms. Notably, the analysis does not include possible effects of these reforms on, e.g., the labour market and/or the housing market, but assesses the ceteris paribus effects of the reforms on the state budget and on poverty and inequality. Depending on the choice of the various parameters of the reforms both the budgetary and the distributional effects may vary widely. We show that the budget deficit may increase or decrease in combination with both increases and decreases in inequality and poverty. So, an optimal tax reform could be chosen depending on the preferences with respect to the budget and the income distribution.
Keywords: D31; H24; I32; 330; Netherlands; income tax; microsimulation; income distribution